Enhancing energy efficiency in pharmaceutical freeze drying: adapting to EU legislation on fluorinated gases - T. Keller; M. Wolf; T. Pröll (International Journal of Thermofluids, 2025)
The pharmaceutical industry relies heavily on freeze-drying technology to ensure the stability and longevity of various medical products. Central to this process is the refrigeration system, which has traditionally depended on fluorinated gases (F-gases) due to their suitable thermodynamic and safety-related properties. However, recent developments in EU legislation, particularly concerning F-gases and per- and polyfluoroalkyl substances (PFAS), necessitate significant adaptations in these refrigeration systems. By exploring an innovative system design, this work aims to identify an opportunity to not only comply with new regulatory requirements but also enhance overall energy efficiency. First, the theoretical potential of the proposed optimization variant is explored. In a second step, the practical influence of heat input from the environment and plant size are considered. Finally, the overall energy consumption during the primary drying stage in comparison to a reference variant is evaluated. The calculations show a promising energy-saving potential, especially for larger plant sizes. Given the complexity of the freeze-drying process, additional questions emerge regarding the feasibility of the approach, taking into account the dynamic nature of the process and the specifics of the product along with other varying process parameters.